Antibacterial activity of the capsules of Moringa oleifera Lamk. (Moringaceae) - Nantachit K. (2017)
This study determined the antibacterial activity of methanolic crude extract, purified dichloromethane extract and isolated parts from column chromatography of Moringa oleifera Lamk. capsules by agar-well diffusion. The methanolic crude extract showed no activity against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Klebsiella pneumoniae ATCC 67120. The purified dichloromethane extract and isolated parts from column chromatography showed antibacterial activity against these bacteria. Antibacterial activity began at 5-10% W/V concentration. It was proved that purified samples consisted of more active components, so they showed antibacterial activity against gram-positive and gram-negative bacteria.